Progresivitas Hukum Pembebanan Nafkah Pasca Cerai Gugat Di Pengadilan Agama Magetan - Siti Wafiroh; Agus Purnomo; Rohmah Maulidia (Journal of Economics, Law, and Humanities, 2023)
Based on the Magetan Religious Court Decision Number 716/Pdt.G/2021/PA. Mgt, whohanded down the verdict, said one of the reasons was to impose a living on the husband. Thedecision is contrary to Article 149 of KHI, which states that the wife who filed for divorcedoes not get a living because the wife is considered nusuz. This research was conducted witha qualitative approach where the data source was taken from direct interviews with theMagetan Religious Court Judge and the Magetan Religious Court decision. The researchresults were described descriptively using words. The results of this study are the basis forconsideration in deciding case Number 716/Pdt.G/2021/PA. Mgt based on the SupremeCourt Circular Number 3 of 2018, the wife in a divorce case can be given mut'ah and iddahas long as it is not proven nusuz and in its proof that it is not proven that the Plaintiff hascommitted nusuz to the Defendant so that the Panel of Judges grants the Plaintiff's claimand in determining the amount of income that the amount of mut'ah is adjusted to theetiquette and ability of the husband so that it does not occur the judgment not executed wasdue to the incompetence of the Defendant. The panel of judges adheres to the progressive legalparadigm and has the courage not to want to mouthpiece the law. This reflects thecharacteristics of progressive law, namely the Judge's decision to follow the situation andcondition of thePlaintiff.